Utilization of Rice Straw, Micro-organisms Effective and Probiotics to Replace Chemical Fertilizers in Fishing Enterprises - Ulul Ilmi; Affan Bachri (Biotropic : The Journal of Tropical Biology, 2018)
Rice straw is a by-product obtained from the harvest of rice. The purpose of this research is to process rice straw into organic fertilizer so it can be used as food source for fishery business. The method used is the experimental method in the field. The results of research that has been done is processing of rice straw able to produce Nitrate (NO3) and zooplankton as a source of organic material that serves as a source of food for fish so that rice straw can serve as a substitute for chemical fertilizer in the fishery business area. By using organic materials, then the fishery business results are more hygienic for consumption and can improve the fishery business.